Study on Effectiveness and Satisfaction of Students with the teaching of Teachers at Savannakhet University - SAIYASAND, Saysamone; XAYAVONG, Somsanouk; PHENGTHONGMA, Phougphet; KEOMANYVONG, Thongma (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This study examines the effectiveness and satisfaction of students with the teaching of teachers at Savannakhet University. The study has three objectives: 1) to study the effectiveness of teachers’ teaching; 2) to study the importance of each factor of efficiency and students’ satisfaction with the teacher's teaching; 3) to study students’ satisfaction with teacher teaching. The sample included 467 students at Savannakhet University. The study tool used in the study was a five-level assessment questionnaire and data analysis consists of two methods, for example, statistical methods and mathematical modeling (Analytic Hierarchy Process: AHP) and Fuzzy Modeling. From the matrix rating, the effectiveness of the teacher’s teaching would be ranked from high to low: The effectiveness of the teachers categorized in the highest level, the activities of the instructional class are the highest and the curriculum is the highest. However, the Media, materials and method for teaching in many respects the learning environment is in the middle. In conclusion, overall, the importance of effectiveness with regard to teachers’ teaching consist of 5 elements are in multiple levels with a value of 3.5528. The satisfaction level of the teachers will be ranked from top to bottom: In terms of teacher effectiveness at the highest level, in terms of teaching activities yes, at many levels comes the media, materials and method for teaching at many levels, the curriculum is at many levels in terms of learning environment, the teaching environment is very hierarchical. In conclusion, overall, the importance of student satisfaction with the teacher’s teaching the 5 elements are in several degrees with the values of 3.5479.